2020
DOI: 10.1039/d0ra04725b
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional graphene–HfS2 van der Waals heterostructure as electrode material for alkali-ion batteries

Abstract: A high rate capacity, moderate volume expansion and energetically stable alkali ion graphene–HfS2 electrode material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 80 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…In order to unveil the underlying enhancement mechanisms, computational approaches have been reported for a number of those 2D heterostructures such as graphene/TMDs, graphene/TMOs, graphene/MXenes, as well as some other graphene-based 2D heterostructures as electrode materials for MIBs. [67,69,76,[78][79][80] According to the computational studies, the key theoretical predictions about graphene-based 2D heterostructures for MIBs can be summarized as: (i) the high electrical-conductivity of graphene could contribute greatly to modify the electronic bonds of the heterostructures due to its unique interlayer interactions which enhance the overall electronic properties (i.e., a robust electronic transport was observed in graphene/MoS 2 , graphene/VS 2, and graphene/HfS 2 heterostructures based anode materials for MIBs, [69,78] as compared to their individual counterparts). (ii) On-surface and interfacial metal-ion adsorption in graphene-based 2D heterostructures is quite high as compared to their single layer nanosheets.…”
Section: Graphene-based 2d Heterostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to unveil the underlying enhancement mechanisms, computational approaches have been reported for a number of those 2D heterostructures such as graphene/TMDs, graphene/TMOs, graphene/MXenes, as well as some other graphene-based 2D heterostructures as electrode materials for MIBs. [67,69,76,[78][79][80] According to the computational studies, the key theoretical predictions about graphene-based 2D heterostructures for MIBs can be summarized as: (i) the high electrical-conductivity of graphene could contribute greatly to modify the electronic bonds of the heterostructures due to its unique interlayer interactions which enhance the overall electronic properties (i.e., a robust electronic transport was observed in graphene/MoS 2 , graphene/VS 2, and graphene/HfS 2 heterostructures based anode materials for MIBs, [69,78] as compared to their individual counterparts). (ii) On-surface and interfacial metal-ion adsorption in graphene-based 2D heterostructures is quite high as compared to their single layer nanosheets.…”
Section: Graphene-based 2d Heterostructuresmentioning
confidence: 99%
“…[84] In addition to Li + and Na + storage, TMDs-based graphene heterostructures have also been proposed as promising materials for other alkali metal ions. King'ori et al [78] reported the energetically favorable and thermodynamically stable of graphene/ Hf 2 heterostructure with K + intercalation in addition to those Li + and Na + . The formation of heterostructure caused a robust electronic behavior due to their lower bandgap and work function of 30 meV and 5.04 eV, respectively, as compared to individual graphene and Hf 2 layers (Figure 4c).…”
Section: Graphene-tmds Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique physical and electrochemical properties of vdW heterostructures make them an intriguing option for potential HER catalysts. In reality, their anisotropic nature makes a pure sample a poor catalytic choice [43][44][45][46]. Atoms are firmly bonded in a satisfied coordination environment leading to an inert structure.…”
Section: Electrochemical Hydrogen Evolution (Her): Vdw Electrodes For Water Splittingmentioning
confidence: 99%
“…HfS 2 , as a member of the transition metal dichalcogenides, has recently emerged as a promising material for electronics and energy conversion applications in the semiconductor community due to its sizeable bandgap and other favorable physical properties. [1][2][3][4][5][6][7][8][9] In comparison to its bulk counterpart, thin film HfS 2 has shown further intriguing properties. 1,10 The methods reported so far for the synthesis of thin film HfS 2 have been mechanical exfoliation and chemical vapor deposition.…”
Section: Introductionmentioning
confidence: 99%